The Research of Auto-Composing Test Paper Technology Based on Genetic Algorithm - Yang, Wei Wei; Song, Hai Feng (Applied Mechanics and Materials, 2014)
In order to meet the demand of test paper in the network test system, the paper establishes test paper mathematical model, uses the integer coding strategy, and applies the improved genetic algorithm to the auto-generating test paper module. The results of the test show that the algorithm can complete the intelligent test paper well, and improve it effectively. Key words: auto-generating test paper; genetic algorithm; fitness function